2018
DOI: 10.1111/ajo.12773
|View full text |Cite
|
Sign up to set email alerts
|

The levonorgestrel‐releasing intrauterine system is associated with a reduction in dysmenorrhoea and dyspareunia, a decrease in CA 125 levels, and an increase in quality of life in women with suspected endometriosis

Abstract: Several favourable outcomes were found following LNG-IUS insertion: (i) dyspareunia and dysmenorrhoea were clearly reduced; (ii) the size of endometriomas were decreased; (iii) CA 125 levels significantly decreased; (iv) a few women experienced the typical systemic adverse effects of progestogens; however, LNG-IUS-related adverse events were generally tolerable and the discontinuation rate was as low as 6.66% (3/45).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 13 publications
0
16
0
2
Order By: Relevance
“…Usually, drugs adopted to treat the chronic pelvic pain are not able to cure women with this problem. Progestins or hormonal contraceptives,3,5 GnRH agonists,6,7 aromatase inhibitors,8 etonogestrel subdermal implant,9 or levonorgestrel-releasing intrauterine devices10,11 are used to counteract the ovarian estrogenic secretion on the endometrium-like tissue developing outside the uterus 12. Even if each of these treatments may be effective and improve quality of life (QoL), pelvic pain usually reappears when women discontinue their usage, thus affecting their QoL.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, drugs adopted to treat the chronic pelvic pain are not able to cure women with this problem. Progestins or hormonal contraceptives,3,5 GnRH agonists,6,7 aromatase inhibitors,8 etonogestrel subdermal implant,9 or levonorgestrel-releasing intrauterine devices10,11 are used to counteract the ovarian estrogenic secretion on the endometrium-like tissue developing outside the uterus 12. Even if each of these treatments may be effective and improve quality of life (QoL), pelvic pain usually reappears when women discontinue their usage, thus affecting their QoL.…”
Section: Introductionmentioning
confidence: 99%
“…Previously Vercellini et al [24] had published a pilot study using LNG-IUD versus expectant management after CS for symptomatic endometriosis with signi cant reduction of dysmenorrhea and risk of recurrence. Subsequently, other studies [9,[25][26][27][28][29][30][31][32] have also shown that LNG-IUD is an effective and well accepted treatment to reduce dyspareunia and dysmenorrhea and increase quality of life in women with suspected endometriosis. However, the long-term maintenance therapy using LNG-IUD after surgery was not effective for preventing endometrioma recurrence [30].…”
Section: Discussionmentioning
confidence: 99%
“…Previously Vercellini et al [32] had published a pilot study using LNG-IUD versus expectant management after CS for symptomatic endometriosis with signi cant reduction of dysmenorrhea and risk of recurrence. Subsequently, other studies [9,[33][34][35][36][37][38][39][40] have also shown that LNG-IUD is an effective and well accepted treatment to reduce dyspareunia and dysmenorrhea and increase quality of life in women with suspected endometriosis. However, the longterm maintenance therapy using LNG-IUD after surgery was not effective for preventing endometrioma recurrence [38].…”
Section: Discussionmentioning
confidence: 99%